Interpretation of “For the First Time” in the the Addenda Regarding the Timeframe of Application of the Treble Damages System: Focusing on the Patent Court Decision No. 2023Na11276 (the Hongsan Gyeonggeumseok case) - Chaho Jung; XueQiong Zhang (Journal of Intellectual Property)
This paper analyzes Patent Court Decision No. 2023Na11276 (the “Hongsan Gyeonggeumseok case”) in the context of determining the applicable timeframe for the treble damages system introduced by the 2019 amendment to the Patent Act. Article 3 of the Addenda to Act No. 16208 stipulates that the enhanced damages system shall apply to infringing acts that occur “for the first time” after the effective date of the amended Act. Previous case law has assigned legal significance to the phrase “for the first time,” holding that the treble damages system does not apply to a single, continuous act of infringement that commenced before the effective date. However, the decision in question interpreted “for the first time” as if it were nonexistent, thereby permitting the enhanced damages system to apply even to infringement that began prior to the effective date but continued thereafter. This paper critically examines the validity of that interpretation. By reviewing the legislative history of the enhanced damages system and evaluating the legal implications of the phrase “for the first time,” this paper proposes the following interpretive approach. Under the principle that a stututory language should be given meaning, the default approach should be to interpret “for the first time” as having meaning. Only when there are reasonable grounds indicating that such an interpretation is undesirable should it be permissible to treat “for the first time” as if it were nonexistent. This paper argues that the court’s decision neglects both the legislative history surrounding the inclusion of “for the first time” in the Patent Act and the necessity for this phrase, thereby committing an error in interpreting the term as if it were nonexistent. It is hoped that this analysis contribute to understanding the meaning of “for the first time” in various other statutes as well.